Financial regulation and supervision across business lines in the United States: Financial holding companies post Gramm-Leach-Bliley Act - Y. Emilie Yoo (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2013)
The financial services industry worldwide has undergone major transformation since the late 1970s. Technological advancements in information processing and communication facilitated financial innovation and narrowed traditional distinctions in financial products and services, allowing them to become close substitutes for one another. The deregulation process in many major economies prior to the recent financial crisis blurred the traditional lines of demarcation between the distinct types of financial institutions, exposing those firms to new competitors in their traditional business areas, while the increasing globalization of financial markets fostered the provision of financial services across national borders. Against this backdrop, a trend toward consolidation across financial sectors as well as across national borders increasingly manifested itself since the 1990s. The developments in the financial markets ever more intensified competition in the financial services industry and induced financial institutions to redefine their business strategies in search of higher profitability and growth opportunities. Consolidation across distinct financial sectors, i.e. financial conglomeration, in particular became a popular business strategy in light of the potential operational synergies and diversification benefits it can offer. This trend spurred the growth of diversified financial groups, the so-called financial conglomerates, which commingle banking, securities, and insurance activities under one corporate umbrella.5 Still today, large, complex financial conglomerates are represented among major players in the financial markets worldwide, whose activities not only sway across traditional boundaries of banking, securities, and insurance sectors but also across national borders. Notwithstanding the economic benefits that conglomeration may produce as a business strategy, the emergence of financial conglomerates also exacerbated existing and created new prudential risks in the financial system. 6 The mixing of a variety of financial products and services under one corporate roof and the generally large and complex group structure of financial conglomerates expose such organizations to specific group risks such as contagion and arbitrage risk as well as systemic risk. When realized, these risks may not only cause the failure of an entire financial group but threaten the stability of the financial system as a whole, as evidenced by the events during recent financial crisis of 2007-2009...
urn:nbn:de:hebis:30:3-332002
Keywords: 330